Advancing Coastal Disaster Governance through Adaptive and Risk-Based Regulatory Reform - Rafi Ramadhan; Sakir (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
Tidal flooding in Pemalang Regency continues to increase due to land subsidence and climate change, while disaster management remains reactive and sectoral in nature, lacking adaptive regulation based on actual risks. This study aims to analyze the strengthening of tidal flood management through the integration of Adaptive Governance and Risk-based Regulation approaches to produce a responsive, collaborative, and risk-based policy model. The study uses a descriptive qualitative method with a case study design through interviews with relevant agencies and affected communities, field observations, and document analysis. The results show that coordination between actors is still hierarchical, policy learning mechanisms do not result in the updating of strategic documents, and risk data is only used as supporting information and has not yet become the basis for binding regulations. In addition, local adaptive capacity has grown but is not yet supported by institutional structures and adequate budgetary provisions. The study concludes that tidal flood governance in Pemalang is in a transitional phase towards a more adaptive system, but requires the strengthening of risk-based regulations, the institutionalization of multi-level collaboration, and periodic policy updates in order to build long-term resilience to tidal flood threats